Projeto de um controlador Fuzzy Takagi-Sugeno para uma estação de tratamento de esgoto por lodos ativados - OLIVEIRA FILHO, José Haroldo Sena de (Universidade Federal do Pará, 2014)
The mean goal of this work is the design of a Takagi-Sugeno fuzzy controller on an activated sludge wastewater treatment plant. This kind of process requires oxygen and aerobic microorganisms in the mixed liquor that are necessary to remove the carbonaceous matter and the nutrients based on nitrogen compounds. The controller acts on the aeration valve engine and has been designed to interpolate the proportional and integrative gain of three fixes controllers designed from the linearization of a continuous model of oxygen mass balance. The controller assists to keep the desirable dissolved oxygen concentration necessary to the nitrification, an oxi-reduction chemical reaction that transforms ammonia into nitrite and it is also possible to save electric energy used by the aeration engine. It is imperative the nitrification occurs for the success of the whole process. The Assays were performed by computerized simulation in four idealized scenarios analyzing the performances of the fuzzy controller and the fix controller designed to a different operation point of the set point defined in the plant. Applying a degree in the set point established in the scenario it was analyzed the rise time, settling time, overshoot and steady-state error. After the assays, the fuzzy controller performed better than the fix one at rise time and settling time criteria and equivalent performance at overshoot and steady-state error. After analysis, it was conclude that the control strategy chosen in the work is viable, according the dissolved oxygen measure at the plant entrance, the fuzzy controller interpolate the proportional and integrative gains of a fix controller designed near this value and thus act quite satisfactory.